On Spectrum of the Weakly Zero-Divisor Graph (Contemporary Mathematics, 2025)
Let us consider the finite commutative ring R, whose unity is 10. The weakly zero-divisor graph, denoted by WΓ(R), is an undirected graph whose distinct vertices c1 and c2 are adjacent if and only if, there exist r ∈ ann(c1) and s ∈ ann(c2) that satisfy the condition rs = 0. This article finds the Seidel Laplacian and Seidel signless Laplacian spectrum for the graph WΓ(Zn) for various values of n.
Keywords: ring of integers modulo n; weakly zero-divisor graph; spectrum of graph; Seidel Laplacian and Seidel signless Laplacian spectrum